2016
DOI: 10.1111/ijd.13223
|View full text |Cite
|
Sign up to set email alerts
|

Building a global teledermatology collaboration

Abstract: Skin disease is common in low-resource countries and is associated with significant morbidity. The disease burden is often heightened by lack of access to adequate diagnosis and treatment. Teledermatology is a growing healthcare delivery modality that allows access to subspecialty care at a distance. This article describes how a low-cost teledermatology program was launched through collaboration between the Medical College of Wisconsin and Hillside Healthcare International. Several factors are required for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…17 As an example, teledermatological models have been explored as a possible means of alleviating the restricted access and reduced costs to dermatologists in Australia. 18 Moreover, a practical aspect of teledermatology has been that it has had a profoundly visual facet intrinsic in its function, 19,20 which has also been inherent within the overall context of telemedicine. 21 This know-how has caused novel opportunities for employing teledermatology in resourcestricken areas.…”
Section: Introductionmentioning
confidence: 99%
“…17 As an example, teledermatological models have been explored as a possible means of alleviating the restricted access and reduced costs to dermatologists in Australia. 18 Moreover, a practical aspect of teledermatology has been that it has had a profoundly visual facet intrinsic in its function, 19,20 which has also been inherent within the overall context of telemedicine. 21 This know-how has caused novel opportunities for employing teledermatology in resourcestricken areas.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of teledermatology, or more specifically store-and-forward applications. These studies have ranged from demonstrating improved access to dermatologic care in medically underserved areas [11][12][13] to shortening consult times in inpatient settings, 14 to providing patients with direct to consumer teledermatology services. 15 Moreover, provider satisfaction has also been shown to be high using store and forward applications.…”
Section: Discussionmentioning
confidence: 99%
“…For the patient data to be secure, the sender and each recipient included must utilize a secure email service. Academic institutions with teledermatology links to developing countries via email platforms include Emory University to a teaching hospital in Kabul, Afghanistan [ 43 ]; the Medical College of Wisconsin to Hillside Healthcare International in Belize [ 44 ]; and the University of Basel, which is linked to several remote clinical sites globally [ 45 ].…”
Section: Types Of Mobile Health (Mhealth) and Telemedicine Toolsmentioning
confidence: 99%
“…Teledermatology methods have been utilized to extend dermatologic care to developing countries since the early 1990s. The benefits of utilizing eHealth technologies are many and reports of successful programs have been published from numerous centers in Africa, Asia, and Latin America [ 5 , 10 , 11 , 44 , 86 , 87 , 88 , 89 ]. The growing transition to mobile teledermatology applications is supported by reports of successful implementation including satisfactory diagnosis and management of skin disease, diagnostic concordance with traditional face to face visits, patient satisfaction and provider satisfaction [ 23 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 ].…”
Section: Benefits and Practical Applications Of Ehealth Toolsmentioning
confidence: 99%
See 1 more Smart Citation